The use of beep-o-grams in the assessment of automatic implantable cardioverter defibrillator sensing function. - Ballas SL; Rashidi R; Mgalister H; Corbelli R; Mccowan R; Wilkoff BL; Castle LW; Morant VA; Simmons TW; Maloney JD (Pacing & Clinical Electrophysiology, 1989)
Noninvasive assessment of sensing performance in the automatic implantable cardioverter defibrillator is limited by the absence of telemetry or memory functions. The adaptation of the electrophysiological test mode into a 'beep-o-gram' recording, with simultaneous audible tones and a surface electrocardiogram, was used in the confirmation of sensing malfunction. Eleven of 13 recordings in patients with documented or clinically suspected inappropriate defibrillator discharges (group 1) demonstrated evidence of definite oversensing. Nonspecific oversensing or undersensing was present in 77% of 27 randomly selected asymptomatic patients without known sensing malfunction (group 2). The sensitivity and specificity for identifying definite oversensing was 85% and 60%, respectively. The beep-a-gram system is a reliable, noninvasive means of confirming sensing malfunction in the automatic impluntable cardioverter defibrillator. Its specificity is limited by the detection of subclinical sensing aberrations, to some degree related to the device's automatic gain control sensing algorithm.